1996
DOI: 10.1111/j.1365-2648.1996.tb02926.x
|View full text |Cite
|
Sign up to set email alerts
|

Burden and health outcomes of family caregivers of hospitalized bone marrow transplant patients

Abstract: Twenty-four family caregivers of bone marrow transplant (BMT) patients were interviewed to describe the burden of care and health outcomes (anxiety, depression, symptom distress and fatigue). A descriptive correlational research design with repeated measures was used. Data were collected in a conference room in the oncology unit of a midwestern university hospital using a battery of questionnaires. Questionnaires were administered pre-BMT (prior to the patient's hospitalization) and 5 and 20 days post-BMT. Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 35 publications
1
75
0
6
Order By: Relevance
“…Conducted studies report that the majority of caregivers experience health issues, domestic problems, and their quality of life decreases. Other studies addressed these problems under categories titled "disturbance", "burden" and "quality of life;" they concluded that the issues they experience were parallel to those experienced by the patient (Foxall and Gaston-Johansson, 1996;Nijboer et al, 1998;Weitzner et al, 1999a;Carter and Chang, 2000;Andrews, 2001;Babaoğlu and Öz, 2003;Borneman et al, 2003;Grunfeld et al, 2004;Carter, 2005;Gaugler et al, 2005;Grov et al, 2005;Dumont et al, 2006;Bostancı et al, 2007;Chang et al, 2007;Chen et al, 2007;Mystakidou et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Conducted studies report that the majority of caregivers experience health issues, domestic problems, and their quality of life decreases. Other studies addressed these problems under categories titled "disturbance", "burden" and "quality of life;" they concluded that the issues they experience were parallel to those experienced by the patient (Foxall and Gaston-Johansson, 1996;Nijboer et al, 1998;Weitzner et al, 1999a;Carter and Chang, 2000;Andrews, 2001;Babaoğlu and Öz, 2003;Borneman et al, 2003;Grunfeld et al, 2004;Carter, 2005;Gaugler et al, 2005;Grov et al, 2005;Dumont et al, 2006;Bostancı et al, 2007;Chang et al, 2007;Chen et al, 2007;Mystakidou et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, both the recipient and caregiver often experience intense emotional distress. [2][3][4] In fact, findings indicate that the level of distress experienced by caregivers often exceeds that of recipients, and they are less likely to obtain mental health intervention. [5][6] Therefore, identifying those variables that may be associated with a high risk for the development of stress-related problems in the caregiving partner is critical to preventive intervention.…”
Section: Introductionmentioning
confidence: 99%
“…18,20 Most data demonstrate that caregivers' levels of anxiety, depression and distress are highest prior to transplant and slowly fall after transplant, although there are little longitudinal data to follow up this after 1 year. 19,22,23 Anxiety is another common symptom among caregivers, often beginning in the pre-transplant period and extending beyond the initial transplant period. 18,21 Depression also affects caregivers of the HSCT population on a frequent basis.…”
Section: Symptoms Of Caregiver Distress and Impact On Family Lifementioning
confidence: 99%
“…18,21 Depression also affects caregivers of the HSCT population on a frequent basis. 21,22 Caregivers also experience physical symptoms and conditions, including fatigue, sleep disturbance, pain, loss of physical strength, loss of appetite and weight loss. 24 One of the most common physical symptoms of caregiver strain is fatigue, 21,22,25 which frequently contributes to poor quality of life even after the acute phase of transplant is complete.…”
Section: Symptoms Of Caregiver Distress and Impact On Family Lifementioning
confidence: 99%
See 1 more Smart Citation